2015
DOI: 10.4014/jmb.1407.07058
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Protective Antigen A in the Pathogenesis of Erysipelothrix rhusiopathiae Strain C43065

Abstract: To clarify the role of surface protective antigen A (SpaA) in the pathogenesis of Erysipelothrix rhusiopathiae C43065 (serotype 2), the spaA deletion mutant of E. rhusiopathiae ΔspaA was constructed by homologous recombination. The virulence of the ΔspaA mutant decreased more than 76-fold compared with that of the wild-type strain C43065 in mice. The mutant strain was sensitive to the bactericidal action of swine serum, whereas the wild-type strain was resistant. The adhesion of wild-type strain to MEF cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…We found that the amino acid sequence of the E. rhusiopathiae SpaA protein predicts a protein structure most closely resembling that of choline-binding proteins of Streptococcus pneumoniae. Indeed, the homology in the C-terminal region of these proteins had previously been described (Borrathybay et al, 2015). This region -containing tandem repeats including the GW motif -is a motif conserved across Gram-positive bacteria that allows proteins to bind to choline residues of techoic acid on the cell surface (Jedrzejas, 2001).…”
Section: Predicted Spaa Protein Structurementioning
confidence: 98%
See 1 more Smart Citation
“…We found that the amino acid sequence of the E. rhusiopathiae SpaA protein predicts a protein structure most closely resembling that of choline-binding proteins of Streptococcus pneumoniae. Indeed, the homology in the C-terminal region of these proteins had previously been described (Borrathybay et al, 2015). This region -containing tandem repeats including the GW motif -is a motif conserved across Gram-positive bacteria that allows proteins to bind to choline residues of techoic acid on the cell surface (Jedrzejas, 2001).…”
Section: Predicted Spaa Protein Structurementioning
confidence: 98%
“…It has been shown that the N-terminal immunoprotective domain of this surface proteinalso referred to as the hypervariable domain -is the component responsible for eliciting protective immunity (Figure 1; Imada et al, 1999;Shimoji et al, 1999). SpaA also plays an important role in pathogenesis by increasing resistance to phagocytosis and promoting endothelial adherence (Harada et al, 2014;Borrathybay et al, 2015;Zhu et al, 2017a,b). Several variants (groups) of the SpaA protein have already been described, based on amino acid differences within the immunoprotective domain (Uchiyama et al, 2014;Janßen et al, 2015;Ogawa et al, 2017).…”
mentioning
confidence: 99%
“…Virulence factor profiles of isolates from terrestrial animals are fairly uniform (Janßen et al, 2015) and include an immunologically significant surface-protective antigen (Spa) for which three isoforms, SpaA, SpaB and SpaC, have been identified (To & Nagai, 2007). SpaA is a common protective antigen of E. rhusiopathiae (Imada, Goji, Ishikawa, Kishima, & Sekizaki, 1999) and virulence determinant that plays a role in cell adhesion, as well as resistance to serum killing and phagocytosis by macrophages (Borrathybay, Gong, Zhang, & Nazierbieke, 2015).…”
mentioning
confidence: 99%
“…However, GAPDH is not the only adhesin of E. rhusiopathiae . Other adhesins, such as SpaA, RspA and RspB [2325], have been reported. Thus, in the competitive adhesion inhibition assay the inhibition was only partial.…”
Section: Discussionmentioning
confidence: 99%